Contribution of horizontal gene transfer to the functionality of microbial biofilm on a macroalgae - Song, Weizhi; Wemheuer, Bernd; Steinberg, Peter D.; Marzinelli, Ezequiel M.; Thomas, Torsten (The ISME Journal, 2021)
Horizontal gene transfer (HGT) is thought to be an important driving force for microbial evolution and niche adaptation and has been show in vitro to occur frequently in biofilm communities. However, the extent to which HGT takes place and what functions are being transferred in more complex and natural biofilm systems remains largely unknown. To address this issue, we investigated here HGT and enrichment of gene functions in the biofilm community of the common kelp (macroalgae) Ecklonia radiata in comparison to microbial communities in the surrounding seawater. We found that HGTs in the macroalgal biofilms were dominated by transfers between bacterial members of the same class or order and frequently involved genes for nutrient transport, sugar and phlorotannin degradation as well as stress responses, all functions that would be considered beneficial for bacteria living in this particular niche. HGT did not appear to be driven by mobile gene elements, indicating rather an involvement of unspecific DNA uptake (e.g. natural transformation). There was also a low overlap between the gene functions subject to HGT and those enriched in the biofilm community in comparison to planktonic community members. This indicates that much of the functionality required for bacteria to live in an E. radiata biofilm might be derived from vertical or environmental transmissions of symbionts. This study enhances our understanding of the relative role of evolutionary and ecological processes in driving community assembly and genomic diversity of biofilm communities.